Reflection of physiotherapy students in clinical placement: a qualitative study - Ayiesah Ramli,; Aida Safra Ruslan,; Noor Shahida Sukiman, (Universiti Kebangsaan Malaysia, 2012)
Clinical education provides students with opportunities to integrate knowledge and skills at progressively higher levels of performance. This study determined the significant events that undergraduate physiotherapy student reflects on during their clinical experiences as they learn to become a physiotherapist. A qualitative study using reflective instruments of structured debriefing sessions and diary writing was carried out. This involves 25 fourth-year students from the Faculty of Health Sciences, UKM   during their 12 weeks of clinical placements in 3 different modules (first semester). They were required to describe an event, its value and their reaction to it, and to discuss the effect of the new learning experience and how it would influence their respond in the future. Our findings confirmed that the process of writing a diary makes a considerable impact to the student experience during clinical placement. The subjects begin to construct a personal identity of becoming a physiotherapist through the process of developing confidence, confirmation of practices and assimilating of knowledge. In conclusion, the main themes   generated from a  reflective diary included their reflection of personal growth, on how they learnt in a clinical setting, and on the ethical and professional behaviors of themselves and colleagues.    This provides the clinical educators with valuable information to design meaningful clinical learning experiences that would assist students to become a good physiotherapist for the future.